(untitled) (European Journal of Marketing and Economics, 2023)
The topic of sustainability, and in particular the sustainability practices of companies, is especially relevant nowadays. The introduction of such practices is very important for Eastern European countries, including Bulgaria. This study is part of a large-scale university project (UNWE, Sofia) that focuses precisely on sustainability practices in international business. The aim is to find out if Bulgarian companies are familiar with sustainable practices and whether they apply them correctly in their daily operations. This is achieved via analysis and synthesis of results from a survey. The summarized data of the aforementioned survey is part of the whole project and represents the policies for sustainable development in specially selected Bulgarian private companies. Each of the companies included in the survey is ISO 14000 certified (the international standards for environmental management) and this condition determines the scope of the study. The research could serve as a basis for better understanding of the integration process of sustainability practices in Bulgarian companies.